(untitled) (Tribhuvan University Journal of Microbiology, 2022)
Objectives: To screen and evaluate antimicrobial activity of crude ethanol extracts against various microorganisms. Methods: Ethanoic extracts of 7 different species; Acorus calamus (Bojho), Aloe vera (Ghiu Kumari), Artermisia indica (Titepate), Azadirachta indica (Neem), Mentha arvensis (Pudhina), Zanthoxylum armatum (Timur) and Zingiber officinale (Ginger) were subjected to soxhlet extraction. Test organisms included mainly enteric isolates i.e. Escherichia coli, Pseudomonas aeruginosa , Klebsiella oxytoca, Salmonella Typhi and Staphylococcus aureus were selected, pathogens confirmed by Antibiotic Susceptibility test was done by disc diffusion method of Modified Kirby – Bauer method using Amikacin (30 mcg), Ampicillin (10 mcg), Chloramphenicol (30 mcg), Ciprofloxacin (5 mcg), Gentamicin (10 mcg) and Penicillin G (10 mcg).The antimicrobial activities of the extracts were determined by Agar well diffusion technique both individually and in combination. On the other hand, Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration was determined by dilution technique. Results: Among 7 plants that were tested, 6 plants were found to have activity against test bacteria. A. calamus was effective against 3 out of 5 test bacteria. A. indica and menthe arvensis inhibited 2 out of 5 bacteria. A. vera and A. indica were effective against S, aureus only and Z. officinale had no antibacterial effects over any tested bacteria. S. aureus was the most susceptible gram positive bacteria meanwhile K. oxytoca stood among Gram negative, emerged as the most resistant species. S. aureus showed ZOI with 6 plant extracts excluding ginger P. aeruginosa was inhibited by A. calamus, A. indica and M. arvensis. The largest ZOI of 15 mm was obtained with Z. armatum acting upon S. aureus. While the smallest diameter of 8 mm was observed with Acorus calamus against S. Typhi. The smallest MBC value of 13.63 mg/ml was obtained with M. arvensis against P. aeruginosa. Results showed that P. aeroginosa was the most resistant bacteria, only 1 out of 3 antibiotics were sensitive to it. 60% of the test bacteria were sensitive to 2 out of 3 antibiotics tested. Conclusion: To recapitulate, the extract of species can be used to prevent the pathogenic organism.